2003
DOI: 10.1063/1.1582393
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of GaNxAs1−x thin films by pulsed laser melting and rapid thermal annealing of N+-implanted GaAs

Abstract: We present a systematic investigation on the formation of the highly mismatched alloy GaN x As 1-x using N + -implantation followed by a combination of pulsed laser melting and rapid thermal annealing. Thin films of GaN x As 1-x with x as high as 0.016 and an activation efficiency of the implanted N up to 50% have been synthesized with structural and optical properties comparable to films grown by epitaxial deposition techniques with similar substitutional N content. The effects of N + implantation dose, laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 26 publications
5
39
0
3
Order By: Relevance
“…2-4 point out, no single crystal has been achieved after LTA annealings, even without ion implantation treatments. This is a striking fact even if we consider that LTA energies used in our experiments are of the order or higher than those values reported for the As-based semiconductors ͑0.2-0.4 J / cm 2 ͒, 26,27 where single crystal regrowth was successfully achieved.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…2-4 point out, no single crystal has been achieved after LTA annealings, even without ion implantation treatments. This is a striking fact even if we consider that LTA energies used in our experiments are of the order or higher than those values reported for the As-based semiconductors ͑0.2-0.4 J / cm 2 ͒, 26,27 where single crystal regrowth was successfully achieved.…”
Section: Resultsmentioning
confidence: 53%
“…25 In fact, using the LTA method, ion implanted amorphized layers of different As-based semiconductors such as GaAs, 25 GaN x As 1−x , 26 and Ga 1−x Mn x As ͑Ref. 27͒ could be recrystallized into single crystal.…”
Section: Resultsmentioning
confidence: 99%
“…The values 5 of the band gap and the line width were determined by fitting the PR spectra to the Aspnes third-derivative functional form. [30] The good epitaxial quality of the GaN x As 1-x layer formed by N + -implantation followed by PLM (0.4 J/cm 2 ) and RTA (950°C for 10-150 s) is confirmed by channeling RBS measurements [28]. Channeling-RBS further reveals that the melt-solid interface occurs at ~200 nm below the surface.…”
mentioning
confidence: 65%
“…Using a pulsed excimer laser, the heavily-damaged layer caused by ion implantation can be melted and recrystallized on time scales on the order of 10 -7 s. Such rapid solidification prevents secondary phase formation even when the equilibrium solubility limit has been exceeded by orders of magnitude [27]. This combined ion beam and laser processing approach has been demonstrated as an effective approach to synthesize dilute semiconductor alloys including GaN x As 1-x and Ga 1-x Mn x As [28,29].Residual damage in the GaN x As 1-x-y P y layers was removed by post-PLM rapid thermal annealing at 950°C for 10-150 sec in flowing N 2 ambient. The crystalline structure of the GaN x As 1-x-y P y samples was studied by channeling Rutherford backscattering spectrometry (c-RBS) and x-ray diffraction.…”
mentioning
confidence: 99%
“…38 Most recently, we have shown that pulsed laser melting (PLM) of N-implanted III-Vs dramatically improves the incorporation of N on the group-V element site. 39,40 In PLM, the near surface absorption of a single intense laser pulse instantaneously melts the implant-damaged or amorphized layer. This is followed immediately by rapid epitaxial regrowth from the liquid.…”
Section: Samplesmentioning
confidence: 99%